2019
DOI: 10.3390/mi10070446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature for Ni/AlOx/Pt RRAM Devices Fabricated with Solution-Based Dielectric

Abstract: Resistive random access memory (RRAM) devices with Ni/AlOx/Pt-structure were manufactured by deposition of a solution-based aluminum oxide (AlOx) dielectric layer which was subsequently annealed at temperatures from 200 °C to 300 °C, in increments of 25 °C. The devices displayed typical bipolar resistive switching characteristics. Investigations were carried out on the effect of different annealing temperatures for associated RRAM devices to show that performance was correlated with changes of hydroxyl group c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 71 publications
0
38
0
Order By: Relevance
“…Therefore, some thin film materials with good electrical conductivity are then chosen as candidates of the electrode, such as pure metal, semiconductor and graphene materials [1][2][3]. For most bipolar RRAM devices, reactive metal like titanium (Ti) [8], nickel (Ni) [9], copper (Cu) [10] and silver (Ag) [11] are always used as TE due to their high metal activity. Compared with reactive metal, where Platinum (Pt) [12] always acts as BE in order to provide activity variation of RRAM devices.…”
Section: Biological (Silk Protein) Polymer (Pvk) Perovskite (Ch3nh3snmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, some thin film materials with good electrical conductivity are then chosen as candidates of the electrode, such as pure metal, semiconductor and graphene materials [1][2][3]. For most bipolar RRAM devices, reactive metal like titanium (Ti) [8], nickel (Ni) [9], copper (Cu) [10] and silver (Ag) [11] are always used as TE due to their high metal activity. Compared with reactive metal, where Platinum (Pt) [12] always acts as BE in order to provide activity variation of RRAM devices.…”
Section: Biological (Silk Protein) Polymer (Pvk) Perovskite (Ch3nh3snmentioning
confidence: 99%
“…Currently, several main fabrication technologies for RS layers have received extensive recognition by researchers, such as atomic layer deposition (ALD), magnetron sputtering, chemical vapor deposition (CVD) and solution-processed deposition. For most inorganic thin film materials used on RRAM devices (such as metal oxides and solid electrolyte), ALD and sputtering are two of the most advanced technologies due to stable performance of RS layers fabricated accordingly [5][6][7][8][9][10][11]. In addition, our previous study indicated that some other fabrication techniques for 2D thin film materials (such as graphene, GO and hexagonal boron nitride (h-BN), h-BN is considered as one of the most promising 2D materials with the function as 2D insulating template for high performance 2D electronic and photonic devices) have also been under intensive consideration, including nucleation and growth, liquid phase exfoliation and electrochemical exfoliation [21].…”
Section: Biological (Silk Protein) Polymer (Pvk) Perovskite (Ch3nh3snmentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) There are also several examples of RRAM and phase-change memories discussed throughout the selected articles. These range from material-and cell-level studies (X. Lian et al [4]; Z. Shen et al [5]; C. Xie et al [6]; and K. Drake et al [7]), to the applications of RRAM in processing of biosignals (Y. K. Lee et al [8]), neural networks (S. Jo et al [9]; and S. N. Truong [10]), and nonvolatile processors (X. Xue et al [11]). (iii) Several of the selected articles discuss new computing paradigms that may take advantage of emerging memory devices (G. Santoro et al [12] and S. Nam et al [13]), as well as extensions, modifications, or innovations in existing volatile and nonvolatile memory technologies (at both the device and circuit levels), which may add new functionalities or improve their performance for computing applications (H. H. Shin et al [14]; S. Yang et al [15]; A. Subbiah and T. Ogunfunmi [16]; H. E. Yantir et al [17]; and L. Gan et al [18]).…”
mentioning
confidence: 99%